RANCANG BANGUN APLIKASI MANAJEMEN TUGAS AKHIR MAHASISWA PROGRAM STUDI TEKNIK INFORMATIKA BERBASIS WEB DI UNIVERSITAS DIAN NUSANTARA – JAKARTA BARAT - Abdullah, Saisa; Rusmawan, Uus (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
In the era of digitization and the advancement of information technology, the final projects at Universitas Dian Nusantara have become a determinant of success in higher education. Although the academic information system SISKA Undira has been helpful, there are deficiencies in final project management. Therefore, this research proposes a web-based final project management application for the Computer Science Program. This application facilitates students, supervising professors, and program coordinators in monitoring and managing final projects. With a focus on prerequisite validation and progress monitoring, this application is implemented using the waterfall method. The goal aims to improve the end project management's efficacy and efficiency. This research provides a relevant and sustainable solution to improve the higher education experience at Universitas Dian Nusantara.